BMPR1A promotes ID2–ZEB1 interaction to suppress excessive endothelial to mesenchymal transition. Issue 3 (27th September 2022) - Lee, Heon-Woo; Adachi, Takaomi; Pak, Boryeong; Park, Saejeong; Hu, Xiaoyue; Choi, Woosoung; Kowalski, Piotr S; Chang, C Hong; Clapham, Katharine R; Lee, Aram; Papangeli, Irinna; Kim, Jongmin; et al.
Abstract: Aims: Components of bone morphogenetic protein (BMP) signalling have been implicated in both pathogenesis of pulmonary arterial hypertension (PAH) and endothelial-mesenchymal transition (EndoMT). In particular, the importance of BMP type 2 receptor in these processes has been extensively analysed. However, the contribution of BMP type 1 receptors (BMPR1s) to the onset of PAH and EndoMT remains poorly understood. BMPR1A, one of BMPR1s, was recently implicated in the pathogenesis of PAH, and was found to be down-regulated in the lungs of PAH patients, neither the downstream mechanism nor its contribution to EndoMT has been described. Therefore, we aim to delineate the role of endothelial BMPR1A in modulating EndoMT and pathogenesis of PAH. Methods and results: We find that BMPR1A knockdown in endothelial cells (ECs) induces hallmarks of EndoMT, and deletion of endothelial Bmpr1a in adult mice ( Bmpr1a iECKO ) leads to development of PAH-like symptoms due to excessive EndoMT. By lineage tracing, we show that endothelial-derived smooth muscle cells are increased in endothelial Bmpr1a -deleted mice. Mechanistically, we identify ZEB1 as a primary target for BMPR1A in this setting; upon BMPR1A activation, ID2 physically interacts and sequesters ZEB1 to attenuate transcription of Tgfbr2, which in turn lowers the responses of ECs towards transforming growth factor beta (TGFβ) stimulation and prevents excessive EndoMT. In Bmpr1a iECKO mice, administering endothelial targeting lipid nanoparticles containing siRNA against Tgfbr2 effectively ameliorate PAH, reiterating the importance of BMPR1A-ID2/ZEB1-TGFBR2 axis in modulating progression of EndoMT and pathogenesis of PAH. Conclusions: We demonstrate that BMPR1A is key to maintain endothelial identity and to prevent excessive EndoMT. We identify BMPR1A-induced interaction between ID2 and ZEB1 is the key regulatory step for onset of EndoMT and pathogenesis of PAH. Our findings indicate that BMPR1A-ID2/ZEB1-TGFBR2 signalling axis could serve as a potential novel therapeutic target for PAH and other EndoMT-related vascular disorders. Graphical Abstract: Graphical abstract